2017
DOI: 10.1680/jgrim.16.00029
|View full text |Cite
|
Sign up to set email alerts
|

Creep improvement factors for vibro-replacement design

Abstract: This work is made available online in accordance with the publisher's policies. Please refer to any applicable terms of use of the publisher. General rightsCopyright for the publications made accessible via the Queen's University Belfast Research Portal is retained by the author(s) and / or other copyright owners and it is a condition of accessing these publications that users recognise and abide by the legal requirements associated with these rights. Although the vibro-replacement stone column technique is be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The creep effect on the settlement performance of stone column in a soft one layer, soil profile was investigated numerically using an isotache-based soil model in combination with the Plaxis 2D FE program. They concluded that stone columns significantly reduced the creep settlement in the long term, but not to the limit of the primary settlement; similarly, conclusions were reached by Sexton and McCabe for a multi-layer soil profile [5,6]. Fattah and Majeed (2012) study the performance of usual and encased floating stone columns under a variety of conditions and discovered that the increase of bearing improvement ratio linked to the increase of length/diameter (L/D) ratio; to the extent when the L/D ratio exceeding the 8 for all the area replacement ratio, also in the case with encasing stone column, there is no practical limit to the L/D ratio.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…The creep effect on the settlement performance of stone column in a soft one layer, soil profile was investigated numerically using an isotache-based soil model in combination with the Plaxis 2D FE program. They concluded that stone columns significantly reduced the creep settlement in the long term, but not to the limit of the primary settlement; similarly, conclusions were reached by Sexton and McCabe for a multi-layer soil profile [5,6]. Fattah and Majeed (2012) study the performance of usual and encased floating stone columns under a variety of conditions and discovered that the increase of bearing improvement ratio linked to the increase of length/diameter (L/D) ratio; to the extent when the L/D ratio exceeding the 8 for all the area replacement ratio, also in the case with encasing stone column, there is no practical limit to the L/D ratio.…”
Section: Introductionmentioning
confidence: 61%
“…The effect of creep on the settlement performance of stone columns is investigated using two groups of analyses: the first group with standard soil criteria from Table 3 and the second group with very low creep coefficients, µ*≤1% of the standard value, effectively reduce the majority of the creep effects. Using of µ*= 0 cannot be used because it results in division by zero [5].…”
Section: 2materials Parametersmentioning
confidence: 99%
“…Similar to the consolidation of soil with the inclusion of vertical drains, stone columns are commonly installed into soft ground in a square or triangular pattern in real practice [8,9]. To develop an equivalent plane strain model, several models from available studies [10][11][12][13] can be applied in which the equivalent geometries or material properties (e.g.…”
Section: Problem Descriptionmentioning
confidence: 99%
“…The Telford Premium Prize, awarded for the best paper on ground improvement, was awarded to Sexton et al (2017).…”
Section: Telford Premium Prize (Best Paper In the Journal)mentioning
confidence: 99%